The Green Man : tales from the mythic forest - Vess, Charles; Windling, Terri; Datlow, Ellen (New York : Viking, 2001)
A collection of stories and poems by a variety of authors relating to the Green Man and other myths of the forest.
Preface / Ellen Datlow and Terri windling -- Introduction / Terri Windling -- Going Wodwo (poem) / Neil Gaiman -- Grand Central Park / Delia Sherman -- Daphne / Michael Cadnum -- Somewhere in my mind there is a painting box / Charles de Lint -- Among the leaves so green / Tanith Lee -- Song of Cailleach Bheur (poem) / Jane Yolen -- Hunter's moon / Patricia Al McKillip -- Charlie's away / Midori Snyder -- A world painted by birds / Katherine Vaz --Grounded / Nina Kiriki Hoffman -- Overlooking / Carol Emshwiller -- Fee, Fie, Foe, et Cetera / Gregory Maguire -- Joshua Tree / Emma Bull -- Ali Anugne O Chash (The Boy Who Was) / Carolyn Dunn -- Remnants / Kathe Koja -- The Pagodas of Ciboure / M. Shayne Bell -- Green Men (poem) / Bill Lewis -- The Green Word / Jeffrey Ford.
Mode of access: Internet.
Keywords: Fantasy fiction, American; Fantasy fiction, English; Forests and forestry -- Literary collections; Green Man (Tale) -- Literary collections